Random Walks in the Representation of Reserves - Ferreira, Manuel Alberto M. (2013)
Models based on Random Walks are presented in this work, to represent reserves. Their main objective is to study and guarantee the sustainability of pensions funds. The use of these models with this goal is a classical approach in the study of pensions funds.